THE IMPORTANCE OF FOOD FOR MULTAR SILKWORMS IN GROWING QUALITY COCOONS (ResearchJet Journal of Analysis and Inventions, 2021)
The article analyzes the impact of mulberry varieties created by our local breeders on the feeding of foreign and domestic silkworms, the impact of their nutritional content on the viability of silkworms during their youth, the cocoon and silkworm cocoons.